"Hole‐Punch" Technique for Recurrent Auricular Hematomas. (21st July 2022) - Lamb, Meredith M; Mims, Mark M; Clark, J. Madison
Abstract : Effective treatment of auricular hematomas can be a challenging problem for both the otolaryngologist and the patient. Recurrence rates are high even with proper drainage and bolstering. The hole‐punch technique is a powerful tool to address the difficult problem of recurrent auricular hematomas and avoid disfiguring deformities of the ear. Laryngoscope, 133:814–817, 2023